Sleep Disorders in Human Immunodeficiency Virus: A Substudy of the Pharmacokinetics and Clinical Observations in People Over Fifty (POPPY) Study. (18th November 2020) - Kunisaki, Ken M; De Francesco, Davide; Sabin, Caroline A; Winston, Alan; Mallon, Patrick W G; Anderson, Jane; Bagkeris, Emmanouil; Boffito, Marta; Doyle, Nicki; Haddow, Lewis; Post, Frank A; Sachikonye, Memory; et al.
Abstract: Background: Self-reported sleep quality is poor in persons with human immunodeficiency virus (PWH), but prior studies commonly used nonspecific questionnaires, investigated only single sleep disorders, or lacked human immunodeficiency virus (HIV)-negative controls. We addressed these limitations in the Pharmacokinetics and Clinical Observations in People Over Fifty (POPPY) Sleep Substudy by assessing PWH and HIV-negative controls for insomnia, restless legs syndrome (RLS), and sleep apnea (SA). Methods: Previously enrolled POPPY participants coenrolled in this substudy without regard to sleep symptoms. Participants completed validated sleep assessments including the Insomnia Severity Index questionnaire, International Restless Legs Syndrome Study Group questionnaire, and in-home, wrist-worn overnight oximetry. They also completed health-related quality of life questionnaires including 36-item Short Form (SF-36) and Patient-Reported Outcomes Measurement Information System (PROMIS) sleep questionnaires. Results: We enrolled 357 PWH (246 >50 years of age; 111 between 18 and 50 years) and 126 HIV-negative controls >50 years of age. Among PWH, criteria were met by 21% for insomnia, 13% for RLS, and 6% for SA. Compared with HIV-negative controls, PWH had a higher risk of insomnia (adjusted odds ratio, 5.3; 95% confidence interval, 2.2–12.9) but not RLS or SA. Compared with PWH without insomnia, those with insomnia reported significantly worse scores on all SF-36 and PROMIS components; fewer than 30% reported previous diagnosis or treatment for insomnia. Conclusions: Insomnia was more common in PWH, associated with worse health-related quality of life, and frequently undiagnosed. Further research should focus on the pathogenesis of insomnia in PWH and the development of effective screening and intervention strategies for this unique population. Abstract : We used validated instruments to concurrently asses for insomnia, restless legs syndrome, and sleep apnea in 357 persons with HIV and 126 lifestyle-matched controls. Insomnia was far more common in HIV, associated with worse quality of life, and frequently undiagnosed.